1990
DOI: 10.2527/1990.6872084x
|View full text |Cite
|
Sign up to set email alerts
|

Particle size reduction during initial mastication of forages by dairy cattle.

Abstract: Four experiments were conducted with dairy cattle to determine the effects of initial feed particle size and moisture content on particle size of ingested masticates. Three mature Holstein cows were used in either latin square or Youden square designs. Samples of masticated and ingested boli were collected at the cardiac opening through a ruminal fistula between 0 and 5, 5 and 10 and 10 and 15 min after meal initiation. In Exp. 1, masticate log mean particle sizes (LMPS) (ln microns, log normal distribution) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 10 publications
4
19
0
1
Order By: Relevance
“…The proportion of large particles larger than 2 mm (LP2) was determined by the sum of the particle proportions retained on 8, 4, and 2 mm aperture sieves, this being considered as the critical size for leaving the reticulo-rumen in cattle [23,28]. As performed by Bailey et al [4], the differences in particle size from feed to bolus and from bolus to rumen were expressed using differences in mean particle size and LP2 proportions.…”
Section: Chemical and Physical Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of large particles larger than 2 mm (LP2) was determined by the sum of the particle proportions retained on 8, 4, and 2 mm aperture sieves, this being considered as the critical size for leaving the reticulo-rumen in cattle [23,28]. As performed by Bailey et al [4], the differences in particle size from feed to bolus and from bolus to rumen were expressed using differences in mean particle size and LP2 proportions.…”
Section: Chemical and Physical Analysesmentioning
confidence: 99%
“…With hays and straws, Lee and Pearce [19] also reported differences in the extent to which roughages were reduced by ingestive mastication. More recently, Bailey et al [4], Bernard et al [6], studied comminution during ingestive mastication with hays with different initial particle sizes. A reduction in particle size was greater with the long than with the short form, 22 vs. 15% [4], 50 vs. 32% [6].…”
Section: Chopping Length and Particle Size Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bailey et al (1990) reported that particle size of ruminal contents had a direct effect on the rate at which diets are passed from the rumen. They suggested that ruminal particle size was a function of the initial particle size of masticated feed and the rate of particle size reduction due to rumination and microbial breakdown.…”
Section: Discussionmentioning
confidence: 99%